The Culture of Organizational Performance Impact of Remote Working: The Case of Yeme Architect - ALKESTID STERJO (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
The Covid-19 pandemic has dramatically changed how organisations oper- ate, receiving attention by many. Remote working entails new norms, which subsequently transform organisational culture that is central to organisational performance. This research explores how this change shapes organisational values that underpins organisational culture, and its effect on employees’ performance. Using a case study of a SME architectural firm in Bradford, UK, qualitative data was gathered through interviews and secondary data, where data was analysed using thematic analysis method. Synthesis suggests, to preserve the existing values, employers should seek to constantly engage with employees through frequent communications, demonstrate actions in favour of the values and reenforce them through reward and recognition. However, new mechanisms to implement this should be identified, given the new working environment (virtual) and different factors affecting employees’ motivation.